Verbalization of Nomadic Culture in Yakut Fairytales - Tomskaya, Maria (Przegląd Wschodnioeuropejski, 2018)
The paper presents a linguocultural study of some aspects of nomadic culture, which are reflected in the texts of the fairytales of the Yakuts. The analysis of Yakut fairytales reveals that their storylines are often centered around the concept of the road – the core element of nomadic culture. The road is viewed as transition, both physical and metaphorical, from the ordinary world to the world of magic. This is the place where the key events of fairytales usually happen. Furthermore, the rites and customs of nomadic people, including the initiation rite, the wedding rite, the traditional holiday of the Yakut horse herders (ysyakh), the horse worship, etc., are represented in the texts of Yakut fairytales. They correspond to the world view of the nomadic Turkic peoples, based on the worship of nature. Nomadic cattle breeding has determined the lifestyle of the Yakuts for many centuries. It resulted in the formation of the principles of life based on archaic mythological concepts – hero, horse, alaas, serge, ysyakh, etc.